Analysis of composition of trees in types of vegetations degenerated by the influence of coal exploitation in Cam Pha town, Quang Ninh province - Hung, Nguyen The (Academia Journal of Biology, 2012)
In recent years, Quang Ninh province has been seriously affected by the environmental degeneration. Especially, Quang Ninh’s forests have deteriorated in both area and quality. Coal mining in Quang Ninh province is considered to be one of main activities that cause loss of forests as well as the biodiversity thereof. Cam Pha town is a region of Quang Ninh on where the coal mining has a heavily destructive impact. Among these types of vegetations, there are 54 wood-stem species belonging to 46 genera and 33 families of the class Dicotyledones of the phylum Angiospermae. The number of species and genera varies in a wide range. The family of Euphorbiceae ranks first in terms of number of species with seven ones. There are four families each of which has three species: Fabaceae, Fagaceae, Rubiaceae and Lauraceae. Seven families each of which contains two species are: Burseraceae, Clussiaceae, Dilleniaceae, Sapotaceae, Symplocaceae, Tiliaceae and Ulmacea. 21 families are left, each with only one species. The family of Euphorbiaceae has five genera, Fabaceae three. Clussiaceae, Fagaceae, Lauraceae, Rubiaceae, Sapotaceae, Tiliaceae and Ulmaceae each have two genera. There are 24 families with only one genus. In Cam Pha town, Quang Ninh province there exists types of vegetations generated by the effect of coal mining with many different levels of degradation. The assemblage of trees of these types consists of 24-47 species, 20-40 genera and 12-29 families, with the average number of genera of one family: 1.37-1.67, the average number of species of one genus: 1.14-1.20, the average number of species of one family: 1.56-2.00. Of Megaphanerophhytes - Mesophanerophytes - MM there are 12-33 species (50-70.21%), the rest are of Microphanerophytes - Mi. Of these types, the major of wood-stem trees are ones able to dwell in intense-lighted areas, grow fast and have a relatively small size. They mainly belong to Euphorbiaceae, Lauraceae, Rubiaceae, Fabaceae, Tiliaceae and Anacardiaceae.